Microstrip leaky wave antenna for wide range of beam scanning in X band - Belen, Aysu; Gunes, Filiz; Belen, Mehmet A.; Mahouti, Peyman (WILEY, 2021)
In this work, design of a pattern reconfigurable antenna is presented for X-band applications as a leaky wave antenna (LWA) realization. Due to the advantages of simple design schematic, low profile, and easy impedance matching, LWA designs have been using as an efficient solution for reconfigurable antenna in many wireless communication applications. Optimization and simulation of the proposed LWA is carried out in 3-D Microwave simulation CST environment and Honey Bee Mating is used as the optimization algorithm. Dimensions of the proposed LWA is 130 x 30 mm, which is fabricated on Rogers 5880 as capacitive loaded eight identical rectangular microstrip patches operating over 9.5-12 GHz with a fractional bandwidth. The proposed LWA exhibits a measured peak gain of 11.8 dBi at 10 GHz with an overall gain characteristic of between 9.5 and 11.8 dBi over the range of 9.5 to 12 GHz with a steerable pattern characteristics between -45 and 50 degrees as agreed with the theory. Furthermore, the fabricated LWA has been found to have the superior performance as compared with its counterparts.
Keywords: beam scanning; leaky wave antenna; microstrip antenna; reconfigurable antenna; MAXIMUM POWER DELIVERY; RADIATION-PATTERN; FREQUENCY; DESIGN; ARRAY; PERFORMANCE; BROADSIDE; Engineering; Optics